Apert Syndrome: Report of a Case with Emphasis on Oral Manifestations - B. Vadiati Saberi; A. Shakoorpour (Tehran University of Medical Sciences, 2011)
To report the oral findings, including dental anomalies, ectopic eruption of the maxillary permanent first molars and periodontal disease and soft tissue alterations, in a subject with Apert syndrome. Clinical and radiographic examination of a patient with Apert syndrome, aged 21 years old, not previously submitted for orthodontic or orthognathic treatment. Dental anomalies were present in a patient. Intraoral evaluation revealed poor oral hygiene with varying degrees of periodontal involvement, an arched swelling (pseudo cleft configuration), class III malocclusion, anterior open bite, posterior crossbite, supernumerary teeth, ectopic eruption and creamy white enamel opacities, an excessively large appearing tongue and a v-shaped maxillary arch. The occurrence of typical lateral palatal swellings agrees with the literature. The high prevalence of dental anomalies and ectopic eruption may suggest a possible etiologic relationship with the syndrome.